Bonds with Variable Coupon as Alternative Source of State Financing for Oil and Gas Industry - V. A. Zaitsev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the problem of searching for financing by companies of oil and gas industry. On the one hand, projects in the industry can be highly beneficial in case of positive macro-economic situation, on the other hand, such projects require serious financing on the investment stage. The goal of the research is to develop an alternative mechanism of financing oil and gas industry by bonds with variable coupon rate, which is based on the interest rate of the Central Bank of the Russian Federation, current prices on crude oil of the Urals brand, base price on crude oil fixed in accordance with the Budget Code of the Russian Federation and actual level of oil production. As a result of the research a mechanism of the floating bond coupon was developed, which is not limited in size in case of high oil prices. This mechanism is based on the current interest rate. Unrecoverable budget losses in the budget system are absent in case of granting standard investment privileges for oil and gas projects. Moreover, if situation in oil prices is positive, state can get higher coupon profit on such bonds. The given type of bonds is an alternative source of financing oil and gas projects on the part of state.